Advancing Educational Practices: Implementing Think-Pair-Share to Achieve Learning Achievement in Islamic Education - Pratama, Ramadhani Yoga; Muhith, Abd; Turmudi, Imam (International Journal of Islamic Studies Higher Education, 2025)
The tendency to apply the lecture learning model in Islamic religious education and ethics lessons can affect student learning results, the matter requires innovation and creation of a teacher so as to be able to implement a cooperative learning model and be able to improve learning results. This study aims to determine the occurrence of increased student learning results through the implementation of cooperative learning models of the think-pair-share type. This research implements a qualitative research method with a type of classroom action research with a Kurt Lewin’s design that model which consists of planning, implementing, observing and reflecting or drawing conclusions. Observation, documentation and testing (pre-test and post-test) are the data collection techniques used in this study. The research instrument used the results of student learning observation sheets and test questions (pre-test and post-test). The research analysis implemented the classical percentage formula. The results showed that students' learning results improved after implementing the cooperative learning model of think-pair-share type, as evidenced by the acquisition of student learning results in cycle I which was 26% while in cycle II 81%. This indicates an increase of 66%. Cooperative learning can enhance students' learning results in Islamic religious education and ethical courses, it might be inferred.